DEVELOPMENT OF KHINA SERIES COCONUT VARIETIES IN INDONESIA - Dr. D. V. Liyanage (International Coconut Community Journal, 1994)
A project for coconut development in Indonesia was initiated in 1972 with assistance from UNDP/FAO and Research Institute for Industrial Crops (LPTI), Bogor as the Counter‑part Agency. Emphasis of research was on breeding and agronomy. Production of KHINA series of coconut varieties was an accomplishment of breeders attached to the project. They were D. V. Liyanage, H. Luntungan, A. Djisbar and T. Mankey. In the initial stages, particularly during germplasm surveys, Ch. P. Corputty and H. Sudasrip were associated. Research on breeding included coconut germplasm surveys in Indonesia, hybridization of selected palms within selected populations and testing progenies. That involved considerable travelling, labour, patience and a barrage of criticism. The agony and joy, breeders experienced in production of KHINA series of coconut varieties are outlined in this paper.